Dynamic Capabilities, Core Competence, and Competitive Advantage of Zakat Institution: Study in Rumah Zakat Indonesia - NUR CHOIRUL AFIF (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
Previous studies of competitive advantage mostly discussed business entities, instead of public organizations or non-profit ones. Several products of public organizations already use a market mechanism such as in the case of zakat collection service in Indonesia. This research investigates the effect of dynamic capabilities and core competence on the competitive advantage of a zakat institution. The data analysis method employed in this research is path analysis to test the direct and indirect effect of dynamic capabilities on competitive advantage. The results of this research show that dynamic capabilities do not directly affect competitive advantage. Dynamic capabilities, however, affect competitive advantage through core competence. Keywords: dynamic capabilities; core competence; competitive advantage; zakat institution